To study the Operating Conditions of Personel Administration of Luang Prabang Teacher Training College - SAIYABOUT, Sakhone; KOUNLAXAY, Kalaphath; SOULIVONG, Phetsamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aimed to (1) study the problems related to the management of staff work performance at Luang Prabang Teacher Training College. The target group of this study consisted of 120 staff at the college, of whom 72 were female. The study employed a survey research design to examine the operational conditions and personnel management of the college. A questionnaire was used as the main data collection instrument. The data were analyzed base on frequency, percentage, mean, and standard deviation to assess the respondents’ opinions regarding the problems managing staff work performance at Luang Prabang Teacher Training College. The research findings revealed that the overall level of respondents’ opinions concerning the issues in staff work management was moderate, with the mean score of and standard deviation as recorded . When analyzed by individual aspects, it was found that all 4 dimensions were rated at a moderate level, namely: The aspect of personnel recruitment and placement obtained a mean score of and a standard deviation of , The aspect of organizational structure and allocation recorded a mean score of and a standard deviation of , The aspect of personnel development showed a mean score of and a standard deviation of , The policy aspect obtained a mean score of and a standard deviation of